2012
DOI: 10.1139/h2012-004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different training programs on antioxidant status, oxidative stress, and metabolic control in type 2 diabetes

Abstract: We compared the effects of 12 weeks of 3 different exercise types on type 2 diabetic (T2DM) male and female human subjects, randomly divided into 4 groups: aerobic training (AT; n = 11), strength training (ST; n = 10), combined training (CBT; n = 10), and no training (NT; n = 12). Metabolic control, anthropometric parameters, lipid and hematological profiles, kidney and liver function markers, hormones, antioxidant enzymes, and oxidative stress markers were assessed prior to and after the training programs. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 51 publications
7
55
0
1
Order By: Relevance
“…Overall, a total of 14 trials (16 reports) extracted from 9,477 articles met the eligibility requirements and were included for the present systematic review and meta-analysis [15][16][17][18][19][20][31][32][33][34][35][36][37][38][39][40]. One study was excluded since it was not described as randomised [41], and two trials provided no information on whether the AET was supervised [42,43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, a total of 14 trials (16 reports) extracted from 9,477 articles met the eligibility requirements and were included for the present systematic review and meta-analysis [15][16][17][18][19][20][31][32][33][34][35][36][37][38][39][40]. One study was excluded since it was not described as randomised [41], and two trials provided no information on whether the AET was supervised [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…To process the data for the meta-analysis, we imputed the data for the changes from baseline means and their SDs. When the SDs for the changes from baseline values were not available [15][16][17][18][19][20], the postintervention values with the corresponding SDs were imputed, according the guidelines of the Cochrane Handbook [13].…”
Section: Data Extraction and Statistical Analysismentioning
confidence: 99%
“…Oxidative stress and elevated ROS generation have been incriminated in many pathological conditions, including diabetes and cancer (14,15). Hypoxia and other adverse stimuli inducing high levels of ROS contribute to endothelium dysfunction and apoptosis in both diabetic retina and tumor microenvironment (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the higher concentration of nitrate in this group, the data suggested that the AE training may improve the antioxidant action and increase the bioavailability of nitric oxide, a potent vasodilator, minimizing the deleterious effects of oxidative stress. So, [18] indicated that this modality may offer additional protection to patients with DM2 due to its antioxidant action [18]. A differential of this work in relation to those published by [16] and Sparks et al (2012) is the shorter period of intervention, which could be insufficient to detect more expressive results, besides the sample selected have a lower body mass index [16][17][18].…”
Section: Discussionmentioning
confidence: 70%